Dawla and Leviathan: Ibn Khaldun and Hobbes in Defense of State Authority - Orwin, Alexander (İbn Haldun Çalışmaları Dergisi, 2018)
Ibn Khaldun and Thomas Hobbes both present the pre-political state as characterized by intolerable violence, and view the establishment of a strong political authority as the best hope of stability. Yet they differ in tracing the origin of this authority. For Hobbes, sovereignty arises due to universal consent and agreement inspired by a collective desire for peace, while for Ibn Khaldun it is consolidated only through the overwhelming power of a tribal feeling known as asabiyya. Modern politics inevitably combines the emphasis on popular consent and law so characteristic of Hobbes, and the tribal feeling, patronage, and special interests so characteristic of Ibn Khaldun.